Strategic Slug Flow Attenuation in Pipeline-Riser Systems - Adegboyega B. Ehinmowo, E.T Evwierhoma, Aliyu M. Aliyu, Osita U Omeje & Frederick Alapa (Covenant Journal of Engineering Technology, 2019)
Oil and gas activities across the globe now take place deep offshore. To operate in this harsh environment, there are numerous challenges. These can be in the form of high cost of production, space constraints, operational and technological demands. The co-transportation of oil and gas in same pipeline is one of the operational and technological approaches adopted in the industry to meet the transportation of produced crude. This approach comes with its attendant flow assurance difficulties. Slugging is one of such problems which can constitute operational hitches resulting in production reduction and sometimes eventual plant shutdown. Existing attenuation techniques are limited in various ways. Therefore, seeking a reliable solution to this problem is highly desired. In this study, an experimental study of multiple techniques for slug attenuation was attempted. A passive device-the intermittent slug absorber, strategically combined with topside choking as well as topside separator were investigated. The theoretical analysis showed that slug attenuating devices can be combined in parallel to reduce the resistance posed on flow, leading to increased flow. The experimental results showed that a combination of the methods proves to be more effective compared to individual techniques. A significant reduction in riser- base pressure of up to 39% was achieved. This is advantageous and translates to an increase in oil recovery. Thus, the proposed strategy helps to achieve system stability and improved production at a lower cost.